Loss of IL-10 Promotes Differentiation of Microglia to a M1 Phenotype - Laffer, Björn; Bauer, Dirk; Wasmuth, Susanne; Busch, Martin; Jalilvand, Tida Viola; Thanos, Solon; Meyer zu Hörste, Gerd; Loser, Karin; Langmann, Thomas; Heiligenhaus, Arnd; Kasper, Maren (Frontiers in Cellular Neuroscience, 2019)
Microglia represent the primary resident immune cells of the central nervous system (CNS) and modulate local immune responses. Depending on their physiological functions, microglia can be classified into pro- (M1) and anti-inflammatory (M2) phenotype. Interleukin (IL)-10 is an important modulator of neuronal homeostasis, with anti-inflammatory and neuroprotective functions, and can be released by microglia. Here, we investigated how IL-10 deficiency affected the M1/2 polarization of primary microglia upon lipopolysaccharide (LPS) stimulation in vitro. Microglia phenotypes were analyzed via flow cytometry. Cytokine and chemokine secretion were examined by ELISA and bead-based multiplex LEGENDplex™. Our results showed that genetic depletion of IL-10 led to elevated M1 like phenotype (CD86+CD206-) under pro-inflammatory conditions associated with increased frequency of IL-6+, TNF-α+ cells and enhanced release of several pro-inflammatory chemokines. Absence of IL-10 led to an attenuated M2 like phenotype (CD86-CD206+) and a reduced secretion of TGF-β1 upon LPS stimulation. In conclusion, IL-10 deficiency may promote the polarisation of microglia into M1-prone phenotype under pro-inflammatory conditions.